(untitled) (Modern education and development, 2025)
Diagnosis of the causes of bleeding, determination of the intensity of intravascular microclotting and disseminated coagulation syndrome (DIC), as well as control of antithrombotic and haemostatic therapy is not possible without special laboratory tests [1,2,3,4].